Taking up the Practice of Study: A Critical Move in the Break of Early Childhood Movement Pedagogies. Issue 3 (2nd July 2020) - Rotas, Nikki; Land, Nicole
ABSTRACT: This article focuses on the speculative practice of "study" in relation to movement pedagogies in early childhood physical education. Bringing the concept in conversation with movement pedagogies, we work to unsettle universalized approaches to early childhood physical education. We orient toward movement pedagogies that refuse the structures of perceptibility that currently formulate movement in childhood places. We speculate how doing movement pedagogies as a study with/in place opens possibilities for moving together. We conclude by offering five propositions for future early childhood pedagogies that centre movement as a practice of study.